2008
DOI: 10.1016/j.ejcts.2007.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Late dialysis rate for coronary artery bypass grafting patients with moderate-to-severe renal impairment: comparison between off-pump and conventional method

Abstract: Patient characteristics, rather than operative strategy of using off-pump or conventional coronary artery bypass grafting, influence the mid-term mechanical renal replacement therapy rate for patients with glomerular filtration rates <60 ml/min.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…There was also a significant difference (0.8% vs. 5.2%) in the rate of commencing dialysis, and the 3-year survival rate was 93% versus 81%, being significantly lower in the mild RD patients (4). In a 4-year post-operative follow-up study, Yu et al (5) found that a pre-operative estimated glomerular filtration rate (eGFR) of 60 ml/min or less was a more important risk factor for postoperative dialysis than the choice of off-pump or on-pump surgery.…”
Section: Discussionmentioning
confidence: 99%
“…There was also a significant difference (0.8% vs. 5.2%) in the rate of commencing dialysis, and the 3-year survival rate was 93% versus 81%, being significantly lower in the mild RD patients (4). In a 4-year post-operative follow-up study, Yu et al (5) found that a pre-operative estimated glomerular filtration rate (eGFR) of 60 ml/min or less was a more important risk factor for postoperative dialysis than the choice of off-pump or on-pump surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A smaller trial that randomly allocated only patients with preoperative renal insufficiency (glomerular filtration rate <60 mL/min/ 1.73 m 2 ) demonstrated reduced rates of short-term (5 days) AKI with OPCAB, 9 with no assessment of longer-term outcomes. In a retrospective study of more than 2000 patients from 2 hospitals in Taiwan, 10 OPCAB was associated with a reduced incidence of short-term (in-hospital) renal failure requiring dialysis in patients with severe renal insufficiency (glomerular filtration rate <30 mL/h), although this effect was lost after controlling for preoperative renal function. No difference was seen in long-term (4-year follow-up).…”
mentioning
confidence: 99%